2019
DOI: 10.3390/cells8121643
|View full text |Cite
|
Sign up to set email alerts
|

STK3/4 Expression Is Regulated in Uterine Endometrial Cells during the Estrous Cycle

Abstract: The uterus is dynamically regulated in response to various signaling triggered by hormones during the estrous cycle. The Hippo signaling pathway is known as an important signaling for regulating cellular processes during development by balancing between cell growth and apoptosis. Serine/threonine protein kinase 3/4 (STK3/4) is a key component of the Hippo signaling network. However, the regulation of STK3/4-Hippo signaling in the uterus is little known. In this study, we investigated the regulation and express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Within the top 1% selection window, a series of genes were identified and found to be deeply involved in animal reproduction and multiple developmental processes. For example, STK3 is a key molecule that connects the downstream signaling pathway of estrogen and the Hippo signaling pathway; it also regulates the dynamic development of the uterine epithelium during the estrous cycle through the signal transduction of uterine epithelial cells (Moon et al, 2019 ). STK3 was annotated to other signaling pathways, such as the MAPK (Bogani et al, 2009 ; Warr et al, 2016 ) and Hippo signaling pathways, that also play an important role in gonadal development and sex determination (Frum et al, 2018 ; Devos et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within the top 1% selection window, a series of genes were identified and found to be deeply involved in animal reproduction and multiple developmental processes. For example, STK3 is a key molecule that connects the downstream signaling pathway of estrogen and the Hippo signaling pathway; it also regulates the dynamic development of the uterine epithelium during the estrous cycle through the signal transduction of uterine epithelial cells (Moon et al, 2019 ). STK3 was annotated to other signaling pathways, such as the MAPK (Bogani et al, 2009 ; Warr et al, 2016 ) and Hippo signaling pathways, that also play an important role in gonadal development and sex determination (Frum et al, 2018 ; Devos et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of STK3/4 and its downstream targets is mediated by p38-MAPK, an estrogen receptor-dependent intracellular signaling pathway. Our previous study showed that the phosphorylation of LATS1/2 was faster than that of STK3/4, which may occur through an unknown signaling pathway for the phosphorylation of LATS1/2 in uterine dynamics during the estrous cycle [ 71 ].…”
Section: Hippo Signaling Factors In the Uterine Endometriummentioning
confidence: 99%
“…The list of genes with contrasting SNPs associated with different reproductive processes included CITED1 (participates in the development of the placenta, as well as in the growth and survival of embryos [99]), CNOT6L (involved in the meiotic cell cycle in mouse oocytes [100]), FNBP1L (associated with male fertility [101]), HERC2 (mutations in this gene lead to sperm acrosome defects, other developmental abnormalities, and juvenile lethality of mice [102]), KMT2D (expressing in male germ cells and regulating spermatogonial differentiation [103]), NFIX (involved in the formation of the synaptonemal complex during male meiosis [104]), PTK7 (involved in the sexually dimorphic development of the genital tract [105]), STK3 (involved in the regulation of dynamic uterine epithelium during the estrous cycle [106]), and TAF9B (involved in mice embryonic germ cell development [107]).…”
Section: Molecular Mechanisms Underlying Speciation Between Cryptic S...mentioning
confidence: 99%